(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the real situation of agricultural injuries in Thai Binh province in 2024. Method: A descriptive cross-sectional study was conducted in 2413 farmers. Results: Among these farmers, 52.2% were 60 years old or above; 45% had other occupations beside farming; the rate of agricultural injuries accounted for 17%; the average number of agricultural injuries was 2.69 ± 1.77; the most common cause of agricultural injuries was sharp objects, accounting for 53.8%. Conclusion: The study shows the rate and causes of injuries in agricultural production, thereby helping departments and agencies strengthen injury prevention solutions in agricultural production activities in Thai Binh province.